Problemy opredeleniâ ponâtiâ i vidovogo sostava istočnikov belorusskogo prava - Silchenko, Nikolay (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The article focuses on different ways of defining the notion and kinds of sources of Belarusian law. The author presents their evolution. Finally, he “discovers” a new approach to religion and precedent as the sources of law in Belarus.
Keywords: prawo białoruskie; źródła prawa; rodzaje prawa; definiowanie pojęć